Penerapan Model UTAUT (The Unified Theory of Acceptance and Use of Technology) Terhadap Minat dan Perilaku Penggunaan Mobile Banking - Widya Anjani; Imam Mukhlis (Jurnal Ekonomi Akuntansi dan Manajemen, 2022)
BRI mobile banking is a form of banking service that provides a strategic role in facilitating customer transaction processes. The development of m-banking BRI service needs to be done by analyzing the factors that motivate of acceptance and use of mobile banking. This reseacrh aims to determine the behavioral intention and use behavior of m-banking BRI in Malang City by applying the UTAUT model. The research approach used by the researcher is quantitative. Then, data collection was obtained through a questionnaire instrument in google form which was distributed to 130 user of m-banking BRI. The sampling technique used purposive sampling method with data analysis by using of multiple linear regression test through Ordinary Least Square (OLS) technique. The results of the research on regression 1 prove that the constructs of the UTAUT model in the form of performance expectancy, effort expectancy and social influence have a positive and significant influence on their relationship with behavioral intention in using m-banking BRI. Meanwhile, the results of the research in regression 2 namely facilitating conditions and behavioral intention are also positive and significant in their influence on the use behavior of using m-banking BRI. Keywords: UTAUT, mobile banking, behavioral intention, use behavior